Conceptual and methodological issues in studying alcohol's harm to others - Room, R.; Laslett, Anne-Marie; Jiang, H. (2016)
While there is a longer history of concern about alcohol's harm to others, researchers' interest has intensified in the last few years. The background of variation in concern over time in different societies is outlined. Three main traditions of research have emerged: population survey studies of such harm from the perspective of the 'other'; analysis of register or case-record data which includes information on the involvement of another's drinking in the case; and qualitative studies of interactions and experiences involved in particular harms from others' drinking. In the course of the new spate of studies, many conceptual and methodological issues have arisen, some of which are considered in the paper. The diverse types of harms which have been studied are discussed. The social and personal nature of many of the harms means they do not fit easily into a disability or costing model, raising questions about how they might best be counted and aggregated. Harm from others' drinking is inherently interactional, and subject to varying definitions of what counts as harm. The attribution to drinking, in the usual situation of conditional causation, is also subject to variation, with moral politics potentially coming into play. For measurement and comparison, account needs to be taken of cultural and individual variations in perceptions and thresholds of what counts as a harm, and attribution to alcohol. The view from the windows of a population survey and of a response agency case register are often starkly different, and research is needed, as an input and spur to policy initiatives, on what influences this difference and whether and how the views might be reconciled.